ANALISIS POTENSI EKOWISATA DI TAMAN WISATA ALAM GUNUNG PANCAR DENGAN MENGGUNAKAN METODE ANALISIS ADO – ODTWA - Imam Ardiansyah; Hari Iskandar (Sekolah Tinggi Pariwisata Mataram, 2022)
Bogor Regency has the potential in developing natural tourism objects and attractions that are scattered in several areas such as the Puncak tourism area, the West part of Bogor Regency, the southern part and the northern part. One of the Nature Tourism Parks which is being developed into ODTWA is the Gunung Pancar Nature Park. TWA has the advantage of the beautiful landscape of pine forest trees around the area. The purpose of this research is to asses the potential and feasibility of ODTWA in TWA Gunung Pancar and analyze what kinds of constraints and problems that arise such as the quality of human resources, advice and infrastructure and other tourism support so that development and development can be directed. This research uses a qualitative approach. Where for qualitative research will analyze the picture based on the fact conditions in the field for the variables studied, the researcher used the Guidelines for the Analysis of the Operational Areas of the Objects and Tourist Attractions. Based on the results of the assessment of ADO ODTWA in Gunung Pancar Nature Park as an ecotourism area with potential and feasible to be developed with a feasibility index of 84.54%. Several indicators need attention for management in carrying out improvements and development to become an ecotourism destination area because they are still in moderate criteria. The indicators in the criteria being assessed for example the condition of the surrounding area, management and services, accommodation, relations with surrounding tourist objects, the carrying capacity of the area and visitor arrangements.